Hungarian Monitoring, 7 April 1988 . [Magyar rádiófigyelő], 1988. április 7 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Gorbachev's London schedule - Ban on churches lifted in USSR - Proposal to cremate Mao Tse Tung's corpse - Exceptional Soviet statement on the shadow economy - American journal on Bulgarian money-laundering - Warsaw Sejm in session Domestic Affairs: - Comecon and Warsaw Pact talks - Hungarian-Israeli diplomatic relations - Hungarian-Soviet relations - National Peace Council holds international conference on alternative military service - Report from meeting of Social Democratic Party's Budapest organization, to which RFE correspondent denied entry - Danube Circle again demands Nagymaros referendum - Ófalu atomic waste burial question Külpolitika: - Gorbacsov londoni programjáról - A SZU-ban feloldották az egyházakra vonatkozó tilalmakat - Javaslat Mao Ce-tung holttestének elhamvasztásáról - Rendhagyó szovjet kimutatás az árnyékgazdaságról - Amerikai folyóirat a bulgáriai pénzmosásról - A varsói szejm üléséről Belpolitika: - KGST és VSZ tárgyalások - Magyar-izraeli diplomáciai kapcsolatok - Magyar-szovjet kapcsolatok - Az alternatív katonai szolgálatról rendezett nemzetközi tanácskozást az Országos Béketanács - Jelentés a Szociáldemokrata Párt budapesti szervezetének üléséről, ahová nem engedték be a SZER tudósítóját - A Duna Kör ismét követeli a népszavazás kiírását Bős-Nagymaros ügyében - Az ófalui atomtemető ügye